Exploring the Layers of Learning: Pop-Up Book as a 3D Bridge to Atmospheric Dynamics - Gisela Noer Ashra; Sumarmi; Zukya Rona Islami; Cut Vita Rajiatul Jummi (Future Space: Studies in Geo-Education, 2025)
This research is based on a needs analysis that shows the limitations of learning aids that can visualize Atmospheric Dynamics material. Therefore, it is expected that there is a practical and effective media to be practiced in learning activities. With this in mind, this research focuses on producing learning media in the form of Pop Up Book that can help students' understanding in learning Atmospheric Dynamics material. The model applied is ADDIE (Analysis, Design, Development, Implementation, Evaluation). Media trials were carried out on class XI IPS 1 at MA Bilingual Batu City. The research findings state that the material feasibility test is 82.5% and the media feasibility test is 100%, so it can be categorized as very feasible to use. The effectiveness test obtained a result of 77% which was categorized as very effective in learning. While the practicality test was obtained from a response questionnaire with a score of 100% from teachers and 87.5% from students, this indicates that the media is categorized as very practical. Based on the test results, the Pop Up Book ‘ATMOGRAF’ media is feasible to be applied as learning media by teachers and students to support the learning process and help students understand Atmospheric Dynamics material.